ANALYSIS OF MASLAHAH MURSALAH REGARDING PRE-MARRIAGE GUIDANCE AS AN ADMINISTRATIVE REQUIREMENT IN EFFORTS TO FORM THE SAKINAH FAMILY ON CONVERTING (STUDY AT KUA SIMPANG EMPAT KARO DISTRICT) - Anasrudin; Milhan; Irwan (Journal of International Islamic Law, Human Right and Public Policy, 2023)
Karo Regency or Tanah Karo is one of the districts in North Sumatra which is inhabited by various religions and beliefs, Islam being the religion of belief for some of its population. Of the various religious groups, religious people are certainly not free from various problems that occur, such as converting from one religion to another religion outside of Islam, as well as adherents of other religions who are moved to learn and join and adhere firmly to the religion of Islam or are also called converts. Recently, it has not only been limited to that, for Muslim converts who want to get married, they have been faced with marriage guidance before marriage as a condition that must be fulfilled, so they have had a little difficulty and quite a few of them have neglected pre-marital guidance when they converted to Islamic teachings. This type of research is classified as qualitative (analytical approach research) with the research approach used being an empirical juridical approach, while the data sources for this research are primary and secondary data sources. The data collection methods used by the author are interviews, documentation and observation. From this research it can be concluded: The implementation of pre-marital guidance for Muslim converts carried out at the KUA Simpang Empat District has gone well. The response of converts to this program is the awareness of the couple regarding their rights and responsibilities as husband and wife. so that in married life an attitude of mutual understanding and mutual respect is formed. The law of carrying out pre-marital counseling for converts to Islam according to the perspective of maslahah murlah is sunnah sukaadah. Premarital guidance is used as a positive administrative requirement, because premarital guidance for converts contains benefits to support the journey to building a household that is sakinah, mawaddah and rahmah.